A COMPARATIVE STUDY OF AUDIO AND VIDEO LISTENING PRACTICES AT THE TENTH GRADE STUDENTS OF A SENIOR HIGH SCHOOL IN PURWAKARTA - Alfikri Hidayatullah; Rahma Sakina; Sri Yunita (Institut Pendidikan Indonesia Garut, 2022)
This research aimed to find out the significant different about video and audio in studentsâ€™ listening practices. This research employed a comparative research design with two group pretest and post-test design. There were two variables: independent variable was video and audio and the dependent variable was the studentsâ€™ listening practices. Population of this study research was 64 students and the samples were 30 students. In collecting the data, the researcher used listening test. Based on the finding of the research, the conclusions can be explained that the first and the second test has different topic and both test has different result of hypothesis testing, which in the first test that discussed the topic about some dialogues and conversations, the t-test value was 13.00 and t-table for n = 58 in level of significant Î± = 0.05 was 2.00. Because of t-test > t-table (13.15 > 2.00), it means that there is a significant difference between the students listening comprehension by using video and audio. Meanwhile in the second test which discussed the topic from cut movie, the t-test value was -10.15 and t-table was 2.00. Because of t-test < t-table (-10.15 < 2.00), it means that there is not a significant difference between the students listening comprehension by using video and audio. The result of this research shows that video is a better media than audio to be applied on student listening comprehension, therefore the implementation of this research expects the teachers/ lecturers to use video as learning media in teaching listening especially in listening comprehension.Â